Identification of Internal Electromagnetic Defects of Implicit-Pole Synchronous Generators Based on the Information of its External Magnetic Field - Morozov A.N.; Kazakov Ju.B.; Morozov N.A.; Nesterov S.A. (Problems of the Regional Energetics, 2022)
The objectives of the work are to develop a non-contact method of detecting internal electro-magnetic defects in synchronous generators based on the analysis of asymmetry of the external magnetic field distribution resulting from damage, establishing the relationship of defects of a generator with the pattern of field distribution, identifying diagnostic signs for the defects. These objectives are achieved by developing and using three-dimensional finite-element models of the external magnetic field of synchronous generators, by studying and analyzing the results of nu-merical simulation of external magnetic fields, by comparing the simulation results with experi-mental data. Significant results of the work include the improvement of the non-contact method for detecting internal electromagnetic defects in synchronous generators, revealing how defects of the generator manifest themselves in the asymmetry of magnetic field distribution, and detect-ing the correlation of field asymmetry with the type and severity of defects. For implicit-pole synchronous generators, it is reasonable to use the field asymmetry coefficient determined by the shift in the magnetic field distribution caused by field coils damage. The sign of the coeffi-cient indicates the pole with a damaged field coil. The value of the coefficient characterizes the severity of damage to the field coils, with a critical value of 0.1. The significance of the results lies in the possibility of timely and non-contact diagnostics of internal electromagnetic defects of implicit-pole synchronous generators, which can significantly reduce the economic damage from failures of generators without installation of diagnostic sensors of damage inside the generators.